2018
DOI: 10.3390/ijms19040948
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Hypoxylonol C and F Isolated from Hypoxylon truncatum against Cisplatin-Induced Cytotoxicity in LLC-PK1 Cells

Abstract: Although cisplatin is the standard platinum-based anticancer drug used to treat various solid tumors, it can cause damage in normal kidney cells. Protective strategies against cisplatin-induced nephrotoxicity are, therefore, clinically important and urgently required. To address this challenge, we investigated the renoprotective effects of Hypoxylon truncatum, a ball-shaped wood-rotting fungus. Chemical investigation of the active fraction from the methanol extract of H. truncatum resulted in the isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Treatment with hypoxylonols D and E, novel benzo[ j ]fluoranthene derivatives, isolated from Annulohypoxylon annulatum , inhibits proliferation of the human umbilical vein endothelial cell line (HUVEC) and human umbilical artery endothelial cell line (HUAEC) as the essential step in tumor angiogenesis [22]. In addition, it has been reported to protect against cisplatin-induced cytotoxicity in the porcine renal proximal tubule epithelial cell line (LLC-PK1) through anti-apoptosis by inhibiting p38, c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase (ERK) phosphorylation and caspase-3 cleavage [23].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with hypoxylonols D and E, novel benzo[ j ]fluoranthene derivatives, isolated from Annulohypoxylon annulatum , inhibits proliferation of the human umbilical vein endothelial cell line (HUVEC) and human umbilical artery endothelial cell line (HUAEC) as the essential step in tumor angiogenesis [22]. In addition, it has been reported to protect against cisplatin-induced cytotoxicity in the porcine renal proximal tubule epithelial cell line (LLC-PK1) through anti-apoptosis by inhibiting p38, c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase (ERK) phosphorylation and caspase-3 cleavage [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, finding the adjuvant agents to reduce cisplatin nephrotoxicity is an important approach for cisplatin cancer therapeutic. Our previous studies had reported other agents from natural products which had potential in reducing cisplatin nephrotoxicity [38][39][40]. In this study, we focused on the renoprotective effect of shikimic acid isolated from A. absinthium on LLC-PK1 cells and mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic cells were measured using a Tali Image-Based Cytometer (Invitrogen) [34]. In brief, cells were harvested after the treatment of 5 mM glutamate for 12 h. The cells were treated with annexin-binding buffer and labeled with AlexaFluor 488-conjugated annexin V for 20 min.…”
Section: Quantification Of Apoptotic Cellsmentioning
confidence: 99%